Electrochemical behaviour of titanium alloys in artificial saliva - DANIEL MARECI (Journal of the Serbian Chemical Society, 2005)
Titanium alloys are used i n odontology applications owing to their excellent biocompatibility. The corrosion resistance of titanium alloys is an important component of their biocompatibility. In this study, the electrochemical corrosion resistance of Ti6Al4V, Ti6Al7Nb, Ti6Al2Nb1Ta1Mo, Ti5Al2,5Fe and commercial titanium in Afnor saliva was investigated. Maintaining titanium and Ti6Al7Nb alloy in Afnor saliva for 7 days results in the formation of a protective layer, the resistance of which is high and could be comparedwith that of a passive layer resulting from electrochemical treatment. The replacement of vanadium with niobium or iron favours the passivation, thus increasing the corrosion resistance.